Prevalence Of Dysmenorrhea Among Adolescent Girls (14-19 Yrs) Of Kadapa District and Its Impact on Quality of Life: A Cross Sectional Study - Kumbhar, Suresh K.; Reddy, Mrudula; Sujana , B; Reddy K, Roja; Bhargavi K, Divya; Balkrishna, C (National Journal of Community Medicine, 2011)
Background: After menarche many adolescent girls faces problems of irregular menstruation, excessive bleeding, and dysmenorrhea. Of these, dysmenorrhea is one of the common problems experienced by most of the adolescent girls. This study conducted to assess the prevalence of dysmenorrhea and its impact on adolescent girls (14 – 19 yrs) Objectives: This study was conducted to estimate the prevalence of dysmenorrhea among adolescent girls (14-19yrs) and also to study the various symptoms of dysmenorrhea and its impact on quality of life of adolescent girls. Materials & methods: This was a cross sectional study conducted from Jan 2011 to May 2011 among 183 Adolescent girls (14-19years) in Schools and colleges Kadapa town using a semi-structured questionnaire. Results: Out of 183 adolescent girls 119 (65%) are dysmennorhic, 68.4% and 61.2% are from the urban and rural areas respectively. Out of 81 adolescent girls with family history of dysmenorrhea 60 (74.1 %) adolescent girls are dysmennorhic. Sickness absenteeism is seen among 47.9% dysmennorhic girls. Quality of life is significantly reduced among dysmennorhic girls. Almost 73.1% of rural girls rely on self-help technique to manage the dysmenorrhea as compare to urban girls(55.2 %) Conclusions: Dysmenorrhea is a very common problem among adolescent girls; it affects their quality of life. It can be better managed by mental preparation and by appropriate change in lifestyle like regular physical exercise and with assurance to the urban girl.